A panel data analysis of the impacts of institutional differences on local governments' budgetary decisions - Soojin Kim; Kim, Eom, Tae Ho (2016)
This study provides empirical evidence on how institutional differences influence school budget decisions by using panel data from 178 K-12 New Jersey school districts for the period 1996 to 2007. The findings obtained by the Newey-West model, correcting heteroskedasticity and serial correlation, support our hypothesis that school districts with elected school boards (Type II districts) are more likely to be effective at lowering school spending than ones with appointed school boards (Type I districts). Viewing school systems through the lens of new institutional economics, this study argues that institutional differences in governance are critical in leading to differences in budgetary decisions by affecting incentive structures faced by public officials, along with transaction costs and agency costs. - Reproduced.
Keywords: Public finance; Local government; Budgets